Examining longitudinal patterns of individual neighborhood deprivation trajectories in the province of Quebec: A sequence analysis application. (November 2021) - Letarte, Laurence; Gagnon, Pierre; McKay, Rachel; Quesnel-Vallée, Amélie; Waygood, E.O.D.; Lebel, Alexandre; ,
Abstract: Exposure to neighborhood deprivation has been associated with a number of health, behavioral and sociological outcomes. However, many negative outcomes associated with deprivation have a long latency and may be influenced by varying exposure to neighborhoods throughout time. Capturing the longitudinal exposure to neighborhood deprivation is methodologically complex when one wishes to include life course notions of order, duration and timing. In a sample of 60, 555 participants, aged 12 years and older (representative of the population of the Province of Quebec in Canada) our objectives were to: 1) Create an indicator for neighborhood deprivation trajectories; 2) compare trajectories with cross-sectional and cumulative neighborhood deprivation; 3) identify individual socioeconomic determinants of membership to a trajectory cluster. Using sequence analysis based on optimal matching and clustering around theoretical types, we grouped sequences in nine neighborhood deprivation trajectory clusters. We found that half (50%) of the participants were in a stable trajectory and did not transition significantly from one deprivation tertile to another during their sequence. A comparison between a cross-sectional indicator of neighborhood deprivation and the trajectories showed that only 42.2% of the participants had a cross-sectional deprivation at the index date representative of their whole trajectory. We also found, using logistic regression (adjusted for age, sex, number of residential moves) that having no high school diploma, living in a rural area and being an immigrant was strongly associated with a deprived stable trajectory. Sequence analysis is an effective tool to describe neighborhood deprivation trajectories in a sample representative of the Quebec population. Trajectories are a useful addition to a better understanding of the distribution of health outcomes because they provide information about the order and accumulation of longitudinal exposures to neighborhood and seem to be associated with specific individual socioeconomic characteristics such as education, urbanity, and immigration status. Highlights: Sequence analysis summarizes longitudinal exposure to neighborhood deprivation. A longitudinal indicator is more representative than a cross-sectional indicator. Neighborhood deprivation trajectory is associated with individual characteristics.